A p–n fusion strategy to design bipolar organic materials for high-energy-density symmetric batteries. Issue 25 (16th June 2021) - Kim, Jihyeon; Kim, Heechan; Lee, Sechan; Kwon, Giyun; Kang, Taewon; Park, Hyeokjun; Tamwattana, Orapa; Ko, Youngmin; Lee, Dongwhan; Kang, Kisuk
Abstract : A new bipolar-type redox-active organic material with a wide HOMO–LUMO energy gap is designed though the 'p–n fusion' strategy. Abstract : Development of a symmetric battery, which employs the same material as both anode and cathode, would significantly simplify the manufacturing process and reduce the production cost, and thus is regarded as a promising alternative approach. Nevertheless, (i) the difficulty in finding suitable bipolar-type active materials and (ii) the low voltage (typically lower than 2 V) from the reported bipolar materials have been the hurdles in its practical realization. Herein, we report a new molecular-level strategy of fusing appropriate p-type and n-type redox materials to develop bipolar-type materials. The inherent potential of each redox reaction in the fused structure is effectively shifted/separated due to the strong mutual electronic perturbation between two motifs, leading to higher voltages achievable in symmetric batteries. We showcase that newly designed PNZTA, a fusion of the phenazine and thianthrene redox centers, successfully manifests the bipolar redox activity and delivers a high discharge voltage of 2.33 V in a symmetric cell, one of the highest values reported thus far. This simple approach of fusion provides a new perspective in the design of high energy density bipolar redox materials and can be applied to a variety of combinations among p-type and n-type organic molecules in exploring high-energy-density symmetric battery chemistry.